STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DALAM PENINGKATAN MOTIVASI KERJA KARYAWAN PADA PT GARUDA KARYA MANDIRI (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to find out what strategies are carried out by the company in this case the human resource management department to increase work motivation at PT Garuda Karya Mandiri. The findings of this study are expected to be able to find out the strategies and steps taken by the company's human resource management to increase work motivation for employees in running the company's organizational wheels. Where we know that in the era of free competition that is so tight today, work motivation that remains high and well maintained will have an impact on achieving optimization of company performance. If this is realized in a company, it can be said that the company will be able to continue to grow, compete and survive very well. In an effort to always maintain employee work motivation so that it is always optimal, a certain strategy is needed by the company's human resource management to make the right steps in increasing employee motivation in the company. The method used in this study is a qualitative method using the motivational theory of Abraham Maslow in seeing and explaining the human need to live. The results of this study found that there were at least three main strategies carried out by the Human Resources Management of PT Garuda Karya Mandiri in increasing employee motivation, namely (1) Compensation Stability Strategy, (2) Firmness Strategy in the Application of Rewards and Punishments, (3) Clarity of Planning Strategy Career path.